Theoretical study of the Structural and Electronic Properties of the Phenol, Phenoxy - A. H. Al-ali , Kawkab (University of Thi-Qar Journal of Science, 2011)
The theortical calculations of phenol, phenoxy, phenol-water complex, phenoxy-watercomplex (I, II, III, IV) were studied by quantum chemical calculations. The optimizedstructures of the compounds were obtained by the Density functional theory (DFT) in gasphase at B3LYP / 6-311G (d, p) & MP2 / 6-311G (d, p) level of theory. The study shown thatthe value of total energy for compound (II) has much more energy and accordingly lessstability in comparison with the compound (I), the compound III (phenol-complex) andcompound IV (pheoxy-complex), have more stable structure than compounds ( I, II ). Inaddition we calculated the HOMO-LUMO, energy gap and system properties such asionization potential (I), hardness (η), electronegetivity(X), electrophilicity (ω). Thecalculation interaction energies show that the compound (IV) showed larger energy thancompound (III). All calculations was carried out for (I, II, III, IV) and shows the favorablestate for stabilities (more stable) (I>II, III>IV).